Memoirs as a Source of Historical Research (Eurasian Journal of History, Geography and Economics, 2023)
Written monuments of personal origin, in other words memoir literature, occupy an important place in the study of the past. They can be called evidence reflecting the reality of the past in writing. Memoir literature is important from the point of view of source studies and is widely used in various fields of humanitarian knowledge. This article discusses the role of memoirs in the truthful reproduction of the past. It is concluded that in the disclosure of a certain event or historical period, memoirs can serve not as secondary, but as the main historical sources